Psychological Conditions of the Appearance of Suicidal Behavior in Adolescents in Terms of Gender - Karshiboeva Gulnoza Abdukadirovna (Open Academia, 2024)
The article highlights the psychological aspects of gender characteristics in suicide. Suicide occurs in society, in relationships between people, due to the presence of problems that a person could not or did not want to solve in the usual, acceptable way, and the presence of anxiety associated with personal unhappiness, despair and depression has been identified. Suicide indicates that in society, in relationships between people, there are problems that a person cannot or does not want to solve in the usual, acceptable way for everyone, there is anxiety about personal unhappiness, despair and depression. Suicide is often caused by longterm illness and sometimes disability. However, most researchers recognize that suicide is the result of a person’s social and psychological maladaptation to external factors. Such a factor can be put forward for any reason that creates conflict in a person, not only in internal, but also in interpersonal relationships. Another problem facing science is related to the early detection of suicidal intentions in a person, especially adolescents.
Keywords: society; relationships; habit; socio-psychological maladjustment